Biodiversity as a cornerstone of agrosystem's sustainability in West Africa - (:unkn) unknown (My University, 2022)
Agrobiodiversity, encompassing crop diversity and the biodiversity that supports agricultural system functioning, plays a major role in agriculture in the context of climate change. This is all the more true in regions like West Africa, where population growth is strong and economic resources are limited. Global models predict average yield loss for major crops of 11% in West Africa by the 2050s. Moreover, climate niches of African crops are expected to shift significantly, reinforcing the need to adapt agricultural diversity and practices. A better use of agrobiodiversity, relying on improved understanding and knowledge of its characteristics, would support greater adaptation and resilience of African agrosystems and food security. Agrobiodiversity, from gene to landscape, is key to achieving food security in the face of the erratic effects of climate change. This chapter highlights novel strategies for agrobiodiversity management and use, while building sustainable and resilient agrosystems for the future of West Africa.
Keywords: African Research